The Influence of Using Crossword Puzzle to Improve Students’ Vocabulary Mastery of Class VII SMP Negeri 4 Pujananting of Barru - Nurfitriani Idris; Muhammad Yahrif; Sujarwo (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
The objective of this study is to find out the influence of crossword puzzle method to improve the students’ vocabulary mastery. This research is quasi-experimental as the design that used two group pretest and posttest. It means that there were an experimental class and a controlled class which were given pretest and posttest. There were 40 students of class VII of SMPN 4 Pujananting of Barru as the sample in this study. The instrument of this research was a written test, to score the students’ vocabulary mastery on pretest and posttest. The result of this research showed that there was a positive effect of the result of students’ vocabulary mastery after using crossword puzzle method. Based on the result of the calculation process the researcher gained that in pretest had a mean of 59,05 and the posttest had a mean of 82,20 of experimental class. Based on the finding of this study, it can be concluded that using of crossword puzzle method in improving students’ vocabulary mastery is quite success. And after conducting the research and calculating the data, it could be stated that it was effective of using crossword puzzle method on students’ of improving vocabulary mastery. Students’ vocabulary mastery got a higher score.